THE EFFECT OF SELF-EFFICACY ON STUDENTS’ LEARNING OUTCOMES AT ELEMENTARY SCHOOL - Nasrah; Novianti; Kaharuddin (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the influence of self-efficacy on students’ learning outcomes. This research was a causal ex-post facto study. The research subjects were elementary school students (SD) with a sample of 27 students. Data collection was carried out using instruments in the form of self-efficacy questionnaires and multiple-choice tests that were developed based on the basic competencies in the cognitive domain to measure science learning outcomes. The results of this study, based on the calculation of the correlation between self-efficacy and learning outcomes, showed a correlation coefficient of 0.029 with p < 0.05. This means that Ho was rejected and Ha was accepted, indicating that students with good self-efficacy tend to achieve higher learning outcomes. The findings confirmed that there is a positive and significant relationship between self-efficacy and student learning outcomes. From these results, it can be concluded that one of the indicators of successful student learning is reflected in the level of self-efficacy. Therefore, this assessment can be used as a basis for teachers to consider solutions and strategies in implementing the teaching and learning process.